Low-level ﬂexible-structure control applied to heat exchanger networks - Giovanini, Leonardo Luis (2003)
A low-level flexible-structure control is proposed for designing control systems capable of efficiently handling constraints on the manipulated variables of heat exchanger networks (HENs). Flexible-structure refers to the capability of the resulting control system to switch from one  closed-loop structure to another in order to keep regulation, and low-level means that it can be configured in most distributed control systems. This control approach is useful to hold the operating point close to an optimum when optimal conditions are located on the constraints. The application example compares the approach with the use of a more involved strategy.